2013
DOI: 10.1186/1471-2393-13-36
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal outcomes in obese mothers: a population-based analysis

Abstract: BackgroundIf it is well known that obesity increases morbidity for both mother and fetus and is associated with a variety of adverse reproductive outcomes, then few studies have assessed the relation between obesity and neonatal outcomes. This is the aim of the present study after taking into account type of labor and delivery, as well as social, medical and hospital characteristics in a population-based analysis.MethodsThis study used 2009 data from the Belgian birth register data pertaining to the regions of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
4
7

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 23 publications
2
38
4
7
Order By: Relevance
“…Saúde Pública 2016; 32(12):e00119015 | www.ensp.fiocruz.br/csp ner, (4) children that received EBF, (5) were born SGA or AGA, and (6) had a 1-minute Apgar score < 7 at birth were less likely to be overweight in the future 19,20,21,22,23,24,25 .…”
Section: Discussionmentioning
confidence: 99%
“…Saúde Pública 2016; 32(12):e00119015 | www.ensp.fiocruz.br/csp ner, (4) children that received EBF, (5) were born SGA or AGA, and (6) had a 1-minute Apgar score < 7 at birth were less likely to be overweight in the future 19,20,21,22,23,24,25 .…”
Section: Discussionmentioning
confidence: 99%
“…These results show the importance of nutrition even during pregnancy which is in agreement with the results of previous studies. In countries with a low or moderate economic status, not only has malnutrition of mothers and infants in the form of underweight not been eradicated, but also the prevalence of malnutrition in the form of overweight and obesity has increased (16). This is also the case among women in the southeast of Iran.…”
Section: Discussionmentioning
confidence: 99%
“…Low weight in mothers before pregnancy causes premature birth and low birth weight (LBW), and increases the risk of perinatal complications, morbidity, and mortality in the mother and infant (6,9). One of the most important complications of obesity during pregnancy is premature birth, prolonged labor (6, 10, 11), perinatal mortality, congenital anomalies (12), increased prevalence of cesarean section (C-section), postpartum hemorrhage (6), low five-minute Apgar score (13,14), its undesirable effects on the later stages of life (15), gestational diabetes, pre-eclampsia (PE), and stillbirths (16). A association has been observed between obesity in the mother and premature birth (17); however, some studies have reported contradictory results (18,19).…”
Section: Introductionmentioning
confidence: 99%
“…26 A recent study using data from a Belgian birth registry revealed an increased adjusted odds ratio for perinatal mortality among obese mothers, though this was not statistically significant. 27 Racial and insurance disparities are recognized as significant predictors of perinatal mortality, preterm birth and death among low-birth-weight infants. 23,24,28,29 Recently, environmental epigenetics, nutritional deficiencies and stress have been suggested as etiologic factors in adverse perinatal outcomes, perhaps mediated by differential inflammatory responses.…”
Section: Discussionmentioning
confidence: 99%